FISIOLOGI PENGUNYAHAN PADA SISTEM STOMATOGNATIFISIOLOGI PENGUNYAHAN PADA SISTEM STOMATOGNATI - Suhartini Suhartini (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2011)
The masticatory system is part of stomatognatic systems that is a functional unit composed of the teeth, the temporomandibular joints, the muscles involved directly or directly in mastication (including the muscles of the lips and tongue) and the nervous systems supplying these tissues. Mastication is the action of breaking down of food, preparatory to deglutition. This breakingdown action is highly organized complex of neuromuscular and digestive activities. Functional and structural disturbance in any one of the components of the masticatory system may be reflected by functional or structural disorders in one or more of its other components. Therefore, it is important that dentists know how mastication normally occurs. This knowledge should ensure that dental procedures improve, rather than reduce, patient's functional abilities.